2007
DOI: 10.1016/j.virusres.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human monocytes after infection by human coronavirus 229E

Abstract: Human coronaviruses (HCoV) are recognized respiratory pathogens that may be involved in other pathologies such as central nervous system (CNS) diseases. To investigate whether leukocytes could participate in respiratory pathologies and serve as vector for viral spread towards other tissues, the susceptibility of human leukocytic cell lines and peripheral blood mononuclear cells (PBMC) to HCoV-229E and HCoV-OC43 infection was investigated. Human primary monocytes/macrophages were susceptible to HCoV-229E infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 74 publications
(81 reference statements)
2
92
1
5
Order By: Relevance
“…In the human airways, HCoV infection may lead to the disruption of the nasal epithelium [250] and, although they bud and are released mostly on the apical side of the epithelial cells, a significant amount of viruses is also released from the basolateral side [251]. Thus, although HCoV infections are, most of the time, restricted to the airways, they may under poorly understood conditions pass through the epithelium barrier and reach the bloodstream or lymph and propagate towards other tissues, including the CNS [33,38,208,252]; this was also suggested for other respiratory viruses that can reach the human CNS, namely, RSV [8,53] [14,220,[252][253][254][255][256]] to manipulate the innate immunity and to disseminate to other tissues, including the CNS, where they may be associated with other type of pathologies, especially in immunocompromised individuals as it was observed for murine cytomegalovirus (MCMV) [257,258]. Moreover, persistently-infected leukocytes [252] may serve as a reservoir and vector for neuroinvasive HCoV [245].…”
Section: Possible Mechanisms Of Hcov Neuroinvasivenessmentioning
confidence: 99%
“…In the human airways, HCoV infection may lead to the disruption of the nasal epithelium [250] and, although they bud and are released mostly on the apical side of the epithelial cells, a significant amount of viruses is also released from the basolateral side [251]. Thus, although HCoV infections are, most of the time, restricted to the airways, they may under poorly understood conditions pass through the epithelium barrier and reach the bloodstream or lymph and propagate towards other tissues, including the CNS [33,38,208,252]; this was also suggested for other respiratory viruses that can reach the human CNS, namely, RSV [8,53] [14,220,[252][253][254][255][256]] to manipulate the innate immunity and to disseminate to other tissues, including the CNS, where they may be associated with other type of pathologies, especially in immunocompromised individuals as it was observed for murine cytomegalovirus (MCMV) [257,258]. Moreover, persistently-infected leukocytes [252] may serve as a reservoir and vector for neuroinvasive HCoV [245].…”
Section: Possible Mechanisms Of Hcov Neuroinvasivenessmentioning
confidence: 99%
“…In the CNS, virus-infected monocytes can propagate neuroinflammation, and therefore neuropsychiatric symptoms, by releasing inflammatory cytokines, and by promoting microglial activation (Hong and Banks, 2015;Wohleb et al, 2015). There is also evidence suggesting that leukocytes can remain persistently infected by CoV (Arbour et al, 2000;Desforges et al, 2007). Therefore, it can be speculated that the timecourse over which CoV-infected immune cells could serve as a potential source of neuroinflammation could be significantly longer than the initial infection and acute symptom presentation.…”
Section: Peripheral Immune Cell Transmigrationmentioning
confidence: 99%
“…This suggests that, even though HCoV infection are, most of the time, self-restricted to the airway lumen since they do not induce important disruption of the epithelium, they may, under certain circumstances, pass through the epithelium barrier and gain access to the bloodstream or lymph, where they can infect leukocytes and consequently disseminate toward other tissues, including the CNS (Fig. 1A; adapted from Desforges et al, 2007;Talbot et al, 2008) as it has been suggested for other important human respiratory viruses; namely measles virus (Wilson et al, 2013), Nipah virus (Mathieu et al, 2011) and influenza B virus (Xu et al, 1998).…”
Section: Possible Mechanisms Of Coronaviruses Neuroinvasivenessmentioning
confidence: 99%
“…Infection of human monocytes/macrophages by HCoV-229E and HCoV-OC43 was reported (Collins, 2002;Desforges et al, 2007) and infection by HCoV-229E of human (Mesel-Lemoine et al, 2012) and murine dendritic cells expressing the human aminopeptidase N (Wentworth et al, 2005) suggests that HCoV may on one hand manipulate the immune system and on the other hand use dendritic cells to disseminate to other tissues, including the CNS, where they could be associated with other type of pathologies.…”
Section: Possible Mechanisms Of Coronaviruses Neuroinvasivenessmentioning
confidence: 99%